Estimation of productive areas of stone pine cone in Portugal with geostatistical tools - Gonçalves A.; Ferreira J.; Godinho-Ferreira P.; Rodrigues A. (Mediterranean pine nuts from forests and plantations, 2017)
This work follows previous field studies aiming to define five different stone pine (Pinus pinea L.) tree developmental stages, of which three corresponded to cone production stages. Based on collected data of cone production of stone pine stands in 40 georeferenced plots and 330 trees in three production campaigns (2004/05, 2005/06 e 2006/07), geostatistical methods of semivariogram and kriging were used to assess the areas of cone productive classes. The study area is located in the region of Setúbal Peninsula in South-Western Portugal, the denominated Provenance Region V, which is the area with the highest cone production in the country. A simple kriging model with a detrended exponential semivariogram was selected and the results of cone productive classes 1 (299-658 kg.ha-1), 2 (122-298 kg.ha-1), and 3 (lower than 112 kg.ha-1), have a potential extent of 345,056 ha, 189,571 ha, and 148,275 ha, respectively. Considering the actual stone pine area the estimated areas of the three productive classes were 23,196 ha, 29,329 ha and 3559 ha for classes 1, 2 and 3, respectively. Further application of geostatistical methodology can be used to evaluate the potential of expansion of stone pine in this region on areas with other land cover types considering cone and/or kernel productive classes.
2. International Meeting on Mediterranean Stone Pine for Agroforestry : AgroPine2016, 2016/05/18-20, Oeiras (Portugal)